Infusing zeta inhibitory peptide into the perirhinal cortex of rats abolishes long-term object recognition memory without affecting novel object location recognition - Augereau, Keanan; Migues, Paola V.; Hardt, Oliver (Frontiers in Behavioral Neuroscience, 2022)
Infusing the amnesic agent zeta inhibitory peptide (ZIP) into the dorsal hippocampus disrupts established long-term object location recognition memory without affecting object identity recognition, which likely depends on the perirhinal cortex. Here, we tested whether infusing ZIP into the perirhinal cortex can abolish long-term memory supporting object identity recognition, leaving long-term object location recognition memory intact. We infused ZIP into the perirhinal cortex of rats either one day or six days after exposing them to two identical objects in an open field arena. One day after ZIP infusion, that is, two or seven days after object exposure, we either assessed whether the animals recognized that now one of the two objects was novel or whether they recognized that one of the two familiar objects was at a new location. Our results show for both retention intervals, infusions of ZIP into the perirhinal cortex impaired novel object recognition but spared novel object location recognition. Rats that received a scrambled version of ZIP had no deficit in either test at both retention intervals and expressed stronger novel object recognition compared to rats infused with ZIP. These findings support the view that object recognition depends on dissociable memory representations distributed across different brain areas, with perirhinal cortex maintaining long-term memory for what objects had been encountered, and hippocampus supporting memory for where these objects had been placed.